The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1095/biolreprod.114.119883
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations Affecting Cholesterol Metabolism and Human Fertility1

Abstract: Single nucleotide polymorphisms (SNPs) represent genetic variations among individuals in a population. In medicine, these small variations in the DNA sequence may significantly impact an individual's response to certain drugs or influence the risk of developing certain diseases. In the field of reproductive medicine, a significant amount of research has been devoted to identifying polymorphisms which may impact steroidogenesis and fertility. This review discusses current understanding of the effects of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…From 2000, ‘gene polymorphism’, ‘DNA fragmentation’ and ‘apoptosis’ emerged as core themes between 2000 and 2004. It indicates researchers understood that these variations or changes in the DNA sequence may significantly contribute to spermatogenesis and germ cell development, and thus have an impact an individual's response to certain drugs or even influence the risk of developing male infertility (DeAngelis et al ., ; Palermo et al ., ; Gunes et al ., ). In the most recent 5 years, ‘ICSI’, ‘IVF’ (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…From 2000, ‘gene polymorphism’, ‘DNA fragmentation’ and ‘apoptosis’ emerged as core themes between 2000 and 2004. It indicates researchers understood that these variations or changes in the DNA sequence may significantly contribute to spermatogenesis and germ cell development, and thus have an impact an individual's response to certain drugs or even influence the risk of developing male infertility (DeAngelis et al ., ; Palermo et al ., ; Gunes et al ., ). In the most recent 5 years, ‘ICSI’, ‘IVF’ (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…There are five classes of LDLR mutations: class 1 mutations affect the synthesis of the receptor in the endoplasmic reticulum; class 2 mutations prevent proper transport to the Golgi body; class 3 mutations stop the binding of LDL to the LDLRs; class 4 mutations inhibit the internalization of the LDLR-ligand complex, and class 5 mutations give rise to LDLRs that cannot recycle properly [12]. Moreover, there are also other genes involved in LDL metabolism, which mutations may result in a phenotype that is clinically indistinguishable from familial hypercholesterolemia such as apo B-100 (APOB-100), proprotein convertase subtilisin kexin type-9 (PCSK9), autosomal recessive hypercholesterolemia (ARH), cholesterol 7alpha-hydroxylase (CYP7A1) deficiencies, and others [13,14].…”
Section: Extreme Hypercholesterolemiamentioning
confidence: 99%
“…SR-B1 expression in ovarian tissue plays a particularly important role in female fertility, as substantial amounts of HDL, are present in follicular fluid surrounding oocytes in ovarian follicles (DeAngelis et al, 2014). During the early phase of follicle maturation, the major steroidogenic cell types were the thecal and interstitial cells, which played crucial roles in controlling follicular growth and atresia, regulating ovarian steroidogenesis and providing supporting structural framework for ovarian follicles (Parrott and Skinner, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Jimenez et al (2010) showed that SR-B1 KO mice had 50% lower serum progesterone levels as compared with wild-type mice. Besides, studies have shown that abnormal SR-B1 expression or function can adversely impact human cholesterol metabolism and fertility (DeAngelis et al, 2014;Yates et al, 2011). However, there was no SR-B1 expression in the granulosa cells at any stage, for its major steroidogenic function was to convert androgens to estrogens (Li et al, 1998).…”
Section: Discussionmentioning
confidence: 99%